Eye blood flow deficiency is the key factor determining the form of the secondary glaucoma in endocrine ophthalmopath - V. G. Likhvantseva; E. V. Korosteleva; I. V. Kovelenova; S. A. Budanova; A. . Ben Regeb (Российский офтальмологический журнал, 2018)
Endocrine ophthalmopathy patients constitute a group of risk for the development of secondary open angle glaucoma (SOAG). Disrupted blood circulation in the main vessels of the eye and the orbit is a mechanism triggering eye hypertension. Purpose: To assess quantitatively the eye blood flow in patients with SOAG developed after endocrine ophthalmopathy. Material and Methods. 48 eyes of SOAG patients averagely aged 42±2.3 years were examined. SOAG, combined with endocrine ophthalmopathy, was characterized by normal eye pressure (63%) and hypertension (37%). Results. The depth and topography of the area with insufficient blood filling may be considered as a key factor that determines the form of SOAG in endocrine ophthalmopathy. Reduced diastole duration, even under longer systole, was found to aggravate ischemia and lead to disturbed blood distribution in the choroid, involving choroid capillaries directly supplying blood to external layers of retina. Conclusions. The reduction of systolic and diastolic phases of the heart cycle leads to grave deficiency of blood filling with predominate ischemia of the anterior segment of the eye, the ciliary body, edema of the trabecula and disturbed intraocular fluid outflow, resulting in the development of ophthalmic hypertension // Russian Ophthalmological Journal, 2016; 3: 43-9. doi: 10.21516/2072-0076-2016-9-3-43-49.